Overlapping Mining Problems With The Right to The Land and The Mechanism of ITS Settlement - Bayu Raharja; Cecep Mochammad Yasin; Yoke Pribadi Kornarius (Publikasi Indonesia, 2023)
The issue of overlapping mining permits with land rights is prevalent in Indonesia. The factors contributing to this overlap problem include disparities or lack of synchronization in basic geospatial information and regulations. The Directorate General of Mineral and Coal has developed a Geological Information System (IGT) for the mining sector with an accuracy of approximately 3 cm, equivalent to a scale of 1:600. This spatial database is further expanded through a web-based application called Minerba One Map Indonesia (MOMI) and Minerba One Data Indonesia (MODI) as the sole recognized source of mining licensing data used by the Central Government and Regional Governments in policy-making. The resolution of overlapping mining permits with forest areas and land rights should still consider business assurance and legal certainty so as not to disrupt the investment climate in the mining sector